Neurological Outcome Following Newborn Encephalopathy With and Without Perinatal Infection: A Systematic Review - Andersen, Mads; Pedersen, Mette Vestergård; Andelius, Ted Carl Kejlberg; Kyng, Kasper Jacobsen; Henriksen, Tine Brink (Frontiers in Pediatrics, 2021)
Background Studies have suggested that neurological outcome may differ in newborns with encephalopathy with and without perinatal infection. We aimed to systematically review this association. Methods We conducted this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Studies were obtained from four databases including Pubmed, Embase, Web of Science, and The Cochrane Database. Newborns with encephalopathy with and without markers of perinatal infection were compared with regards to neurodevelopmental assessments, neurological disorders, and early biomarkers of brain damage. Risk of bias and quality of evidence was assessed by the Newcastle-Ottawa scale and Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results We screened 4284 studies of which eight cohort studies and one case-control study met inclusion criteria. A narrative synthesis was composed due to heterogeneity between studies. Six studies were classified as having low risk of bias, while three studies were classified as having high risk of bias. Across all outcomes, the quality of evidence was very low. The neurological outcome was similar in newborns with encephalopathy with and without markers of perinatal infection. Conclusions Further studies of higher quality are needed to clarify whether perinatal infections may affect neurological outcome following newborn encephalopathy.